(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
In developing countries, road traffic accidents (RTAs) are major health problem accounting for maximum mortality and morbidity following head injuries. The incidence of head injuries due to RTAs are growing with great increase in high velocity transport throughout the world posing itself as a major epidemiological and medico legal problem. The present prospective study was done at Department of Forensic Medicine & Toxicology, B. J. Medical College, Ahmedabad from January 2014 to December 2014. Out of 4137 medico-legal autopsies conducted during the study period, 302 cases of RTAs cases we have studied. The present study reveals that head injury is the common cause of death. It was noted that male of age group of 21-40 years are more affected. Most common place of occurrence of RTAs is main road which comprise 61.26% of cases of RTAs. RTAs 65.56% were those of two wheeler motor vehicle occupants and 25.17% were those of pedestrians, 9.27% were those of four wheelers occupants. 48.01% cases there was history of head on collusion and in 25.17% of cases pedestrians were hit by the vehicles, 16.22% of cases were those of skid and 10.60% of cases were hit and run over. Shock and haemorrhage due to head injury is main cause of death in 226 cases out of total 302 cases.